Effect of dihydrotestosterone on cultured human tenocytes from intact supraspinatus tendon - Denaro, Vincenzo; Ruzzini, Laura; Longo, Umile Giuseppe; Franceschi, Francesco; De Paola, Barbara; Cittadini, Achille; Maffulli, Nicola; Sgambato, Alessandro (Knee surgery, sports traumatology, arthroscopy : official journal of the ESSKA, 2010)
The role of hormones in the pathogenesis of tendinopathy is not well recognised, even though the use of anabolic steroids is correlated with a higher incidence of spontaneous tendon ruptures. The aim of this study was to investigate the effects of dihydrotestosterone (DHT) on human tenocyte cultures from the intact supraspinatus tendon of male subjects. Cultured human tenocytes were seeded into culture plates at a density of 5 × 10 4 cells per well and incubated for 24 h. Then, 10 −9 M–10 −7 M DHT or Dulbecco’s modified Eagle’s medium (DMEM) only (control) was added to the culture plate wells. Cell morphology assessment and cell proliferation tests were performed 48, 72 and 96 h after DHT treatment. DHT-treated tenocytes showed an increased proliferation rate at DHT concentration higher than 10 −8 M. Differences in cell numbers between control and DHT-treated cells were statistically significant ( P < 0.05) after 48 and 72 h of treatment with DHT concentrations of 10 −8 and 10 −7 M. The tenocytes treated with DHT (10 −8 and 10 −7 M) became more flattened and polygonal compared to control cells that maintained their fibroblast-like appearance during the experiment at each observation time. In conclusion, in vitro, progressive increasing concentration of DHT at doses greater than 10 −8 M had direct effects on male human tenocytes, increasing cell number after 48 and 72 h of treatment, and leading to a dedifferentiated phenotype after 48 h of treatment. This effect can be important during tendon-healing and repair, when active proliferation is required. Our results represent preliminary evidence for a possible correlation between testosterone abuse and shoulder tendinopathy.